Controversial Role of the Immune Checkpoint OX40L Expression on Platelets in Breast Cancer Progression - Rittig, Susanne M.; Lutz, Martina S.; Clar, Kim L.; Zhou, Yanjun; Kropp, Korbinian N.; Koch, André; Hartkopf, Andreas D.; Hinterleitner, Martina; Zender, Lars; Salih, Helmut R.; Maurer, Stefanie; Hinterleitner, Clemens (Frontiers in Oncology, 2022)
In conventional T cells, OX40 has been identified as a major costimulating receptor augmenting survival and clonal expansion of effector and memory T cell populations. In regulatory T cells (Treg) OX40 signaling suppresses cellular activity and differentiation. However, clinical trials investigating OX40 agonists to enhance anti-tumor immunity, showed only limited success. Here we show that platelets from breast cancer patients express relevant levels of OX40L and platelet OX40L (pOX40L) inversely correlates with platelet-expressed immune checkpoint molecules GITRL (pGITRL) and TACI (pTACI). While high expression of pOX40L correlates with T and NK cell activation, elevated pOX40L levels identify patients with higher tumor grades, the occurrence of metastases, and shorter recurrence-free survival (RFS). Of note, OX40 mRNA levels in breast cancer correlate with enhanced expression of anti-apoptotic, immune-suppressive, and tumor-promoting mRNA gene signatures. Our data suggest that OX40L on platelets might play a diverse role in cancer and anti-tumor immunity. Since pOX40L reflects disease relapse better than the routinely used predictive markers CA15-3, CEA, and LDH, it could serve as a novel biomarker for refractory disease in breast cancer.